2016
DOI: 10.1016/j.epsl.2016.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal seismological and magmatic processes controlled by the tearing South American flat slabs

Abstract: 8The influence of flat slab subduction on the formation of intra-slab 9 earthquakes, volcanic activities and mantle seismic velocity anomalies remains 10 unclear. We attempt to better understand these processes by simulating the two flat 11 slabs in Peru and Chile using data-orientated geodynamic models. Our results 12 successfully reproduce the observed flat slabs as mainly due to two subducting 13 aseismic ridges. In contrast to the traditional view of flat-slab subduction, we find 14 that these slabs are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
55
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 63 publications
5
55
0
Order By: Relevance
“…A possible example of a deep Nazca slab conduit, although of uncertain origin, facilitating such mantle flow can be found in recent tomography57 of the Nazca slab under the Bolivian Orocline, Central Andes, where below depths of 600 km an eastward pointing cusp in slab geometry is identified that seems associated with a hole in the slab. This deep tear in the slab may perhaps have a geometrical (lateral slab bending) origin as it also occurs as such in recent 3-D modelling of the Nazca subduction45. An overview of SKS splitting results58 shows anomalous and puzzling E-W fast splitting patterns in the subslab mantle59 in a narrow zone (∼150 km in N-S extent) that geographically aligns in E-W direction with the deep slab hole.…”
Section: Discussionmentioning
confidence: 73%
“…A possible example of a deep Nazca slab conduit, although of uncertain origin, facilitating such mantle flow can be found in recent tomography57 of the Nazca slab under the Bolivian Orocline, Central Andes, where below depths of 600 km an eastward pointing cusp in slab geometry is identified that seems associated with a hole in the slab. This deep tear in the slab may perhaps have a geometrical (lateral slab bending) origin as it also occurs as such in recent 3-D modelling of the Nazca subduction45. An overview of SKS splitting results58 shows anomalous and puzzling E-W fast splitting patterns in the subslab mantle59 in a narrow zone (∼150 km in N-S extent) that geographically aligns in E-W direction with the deep slab hole.…”
Section: Discussionmentioning
confidence: 73%
“…Such a tear can form independently of the material below the slab yet would allow any buoyant material below the slab to rise into the mantle wedge. While our tomography model is the first to image this process at the JFR, such tearing was recently modeled in a continent‐scale simulation of Nazca slab subduction [ Hu and Liu , ; Hu et al ., ], supporting the second end‐member model for tear formation.…”
Section: Discussionmentioning
confidence: 90%
“…In this case, the tear formed due to buoyancy contrasts within the slab. Intraplate buoyancy contrasts have been invoked to induce tearing in a variety of settings involving crustal thickness variations within the subducting slab [ Pennington , ; Gutscher et al ., ; Hu and Liu , ]. The subducted JFR is likely at least 13 km thick [ Gans et al ., ], which is thick enough to lead to neutral‐positive buoyancy of the local subducting Nazca slab [ Gutscher et al ., ].…”
Section: Discussionmentioning
confidence: 99%
“…An implicit assumption is that the slab pull that drives continued subductions comes from adjacent regions with a negatively buoyant oceanic plate (e.g., van Hunen et al, 2002). However, these models cannot be used to assess how along-strike factors, such as variations in oceanic and continental structure and along-strike mantle flow, may affect the dynamics (e.g., Hu & Liu, 2016;Martinod et al, 2005;Taramón et al, 2015). The flat-slab segments in nature have a limited along-strike extent.…”
Section: Model Limitationsmentioning
confidence: 99%